Safety of vaginal disinfection with 3% alcohol iodine solution after cesarean section: thyroid function assessment in postpartum women with no risk factors for thyroid gland - Orlicz-Szczęsna, Grażyna; Biłan, Andrzej; Zdanowska, Jolanta (Current Problems of Psychiatry, 2011)
Objective: To prospective evaluate the influences of vagina desinfection with 3% alcohol iodine solution on thyroid function in puerperium women living in areas with iodine sufficient supplementation.Study design: Thirty one females with no personal and familiar history of thyroid diseases underwent vaginal disinfection with 3% alcohol iodine solution after cesarean section. The study finished twenty eight of them. All females we sampled for TSH and FT4 before cesarean section, after one and three months respectively.Results: The mean TSH and FT4 levels of analyzed group stayed in laboratory normal range. Fourteen percent of examined puerperium women developed TSH level depresion. One patient expand overt hypothyroidism (3.5%).Conclusions: Women after administration of large amount of iodine should be under accurate control in puerperium period.